Prevalence of hypertension and co-morbidities among elderly women in rural area: a cross sectional study - M. N., Soumyashree; Viveki, R. G. (International Journal Of Community Medicine And Public Health, 2018)
Background: NCDs have been the leading causes of death among women globally for the past three decades and are now responsible for two in every three deaths among women each year. India endorsed the Sustainable Development Goal for health to set a target to decrease premature deaths from non-communicable diseases (NCDs) by one-third by 2030. Aims of the study were to estimate the prevalence of hypertension among the elderly women from rural area and to know the associated co-morbidities among the elderly women from rural area. Methods: A community based cross sectional study was conducted among elderly women >60 yrs. Data was collected by using pre tested structured questionnaire, which contained basic information like name, age, education & socioeconomic status, occupation, marital status, known case of hypertension, family history, any other co- morbidities. Results: 65.2% of the participants had normal blood pressure, 34.7% were hypertensive. 38% of study subjects living in joint family were hypertensive, majority (53.8% and 85.6%) of them who were obese and had a history of tobacco intake were hypertensive. The association between hypertension and these variables was found to be statistically significant. Conclusions: 15.4% of the study participants were newly detected hypertensives. This indicates a need for awareness to be created among the elderly women regarding hypertension risk factors, to sensitize them for regular medical check-ups to ensure prevention and early detection of hypertension.